5+7x=9x-12

Simple and best practice solution for 5+7x=9x-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+7x=9x-12 equation:


Simplifying
5 + 7x = 9x + -12

Reorder the terms:
5 + 7x = -12 + 9x

Solving
5 + 7x = -12 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
5 + 7x + -9x = -12 + 9x + -9x

Combine like terms: 7x + -9x = -2x
5 + -2x = -12 + 9x + -9x

Combine like terms: 9x + -9x = 0
5 + -2x = -12 + 0
5 + -2x = -12

Add '-5' to each side of the equation.
5 + -5 + -2x = -12 + -5

Combine like terms: 5 + -5 = 0
0 + -2x = -12 + -5
-2x = -12 + -5

Combine like terms: -12 + -5 = -17
-2x = -17

Divide each side by '-2'.
x = 8.5

Simplifying
x = 8.5

See similar equations:

| Log(x)12=5 | | y*(-3-y)=-10 | | -3y-y=-10 | | 15y-y=56 | | 3x^2-6x+1.625=0 | | f(1/2x)*(1/2x) | | 681=X+0.3X | | (0.45*1.6x)+(0.55*x)=6 | | (14/120)x(14/120)x(14/120) | | (0.45*1.6x)+(0.55*x)=3 | | 4x-9=ax-3a | | 4x-9=ax-3ax | | 4x-9=ax-3 | | 54-12x=16x+10 | | (0.6*2x)+(0.4*x)=6 | | X^2+y^2=6z | | 2=-x-1 | | 1=-x-1 | | z^3=-81 | | 3=4-2y | | 1=4-2y | | 3(3x+2)=11x+4-2x+2 | | (1*2x)+(1*x)=12 | | (1.2*2x)+(0.8*x)=12 | | 2x(x+2)(x+6)=0 | | (1.2*2x)+(0.8*x)=6 | | Factorizem^3+5m^2=0 | | 1.2*2x+0.8*x=6 | | 7x+5y=115x+7y=13findx+y | | 2x^2+5x-k=0 | | 4y+Z-23=40 | | Y=50-1.5(10) |

Equations solver categories